2013
DOI: 10.5005/jp-journals-10001-1157
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cytodiagnosis of Head and Neck Neoplastic Lesions and Comparison with Histopathology

Abstract: Introduction: The development of aspiration cytology is one of the biggest advances in anatomic pathology. Cancer has become one of the 10 leading causes of death in India. Head and neck neoplasia is a major form of cancer in India, accounting for 23% of all cancers in males and 6% in females. The advantages of fine needle aspiration cytology (FNAC) are: it is safe, sensitive and specific for the diagnosis of malignancy, gives a rapid report, requires little equipment, causes minimal discomfort to the patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…4,5 Common benign and inflammatory lesions of head and neck region include various cysts and swellings of skin and subcutaneous tissues, Koch's and other inflammations, goiter, salivary gland swellings, lymphadenitis and oral lesions. 5,6 Malignancies in head and neck region are the tenth most common cancers in the world and are an important cause of morbidity and mortality in affected patients. 3,7 Malignant lesions can present as primary as well as secondaries from other organs.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Common benign and inflammatory lesions of head and neck region include various cysts and swellings of skin and subcutaneous tissues, Koch's and other inflammations, goiter, salivary gland swellings, lymphadenitis and oral lesions. 5,6 Malignancies in head and neck region are the tenth most common cancers in the world and are an important cause of morbidity and mortality in affected patients. 3,7 Malignant lesions can present as primary as well as secondaries from other organs.…”
Section: Introductionmentioning
confidence: 99%
“…Mapping patterns of head and neck cancers of 18 months prospective and cross sectional study 60 patients have been diagnosed and confirmed histopathologically as cancers, these cases were plotted as per topographic codes and the leading topographic site was upper aero digestive tract, followed by thyroid cancers, in addition to thyroid cancers few miscellaneous leading sites are added which are salivary glands cancers, skin +subcutaneous cancers and lymphatic cancers, so aerodigestive tract in present study (Table 5) reduced to 66.67% [4],while in previous study it was about 100%. Aero digestive tract cancers are common in all studies by using topography mapping.…”
Section: Discussionmentioning
confidence: 62%
“…1,2 It is an inexpensive and safe outpatient procedure that provides a rapid diagnosis and requires minimal equipment. 3 Also, it offers high sensitivity and specificity in the evaluation of cutaneous and subcutaneous masses. [4][5][6] Scalp lesions are frequently encountered in clinical practice and comprise a spectrum of nonneoplastic and neoplastic pathologies.…”
Section: Introductionmentioning
confidence: 99%